Nutrient upcycling and flows of carbon, nitrogen, and phosphorus in Hediste diversicolor (OF Müller, 1776) (Annelida: Nereididae) fed aquaculture sludge - Anglade, Inka; Sæther, Håkon O. E.; Hagemann, Andreas; Reitan, Kjell Inge; Malzahn, Arne M. (Frontiers in Marine Science, 2024)
Introduction With the continuous growth of Atlantic salmon (Salmo salar L.) aquaculture, appropriate management of nutrient-rich waste streams from both land- and sea-based production has become increasingly important. Following a circular approach, nutrients contained in aquaculture sludge can be utilized for biomass production of the polychaete Hediste diversicolor. While the potential for upcycling nutrients has been established previously, this study aimed to assess nutrient flows in H. diversicolor fed aquaculture sludge as understanding these will be crucial for optimizing future large-scale production of this species. Materials and methods We investigated the effect of low and high feed supply of smolt sludge on the nutrient flows of carbon (C), nitrogen (N), and phosphorus (P) in H. diversicolor on an individual level. Hereby we assessed ingestion, defecation, excretion, respiration, and uptake for growth. Results and discussion Nutrient flows differed between the nutrients C, N, and P in the high feed supply group where C uptake for growth was significantly higher than N and P uptake, and N uptake was significantly higher than P uptake. In contrast, no significant differences were observed in the low feed supply group. In the high feed supply group, most of the ingested C, N, and P by H. diversicolor was allocated to uptake for growth (76% C, 83% N, 85% P) with smaller proportions allocated to defecation (7% C, 7% N, 11% P) and respiration/excretion (18% C, 9% N, 5% P). The results from the low feed supply group suggest insufficient nutrient supply as most ingested C was allocated to respiration (84%), while most N was expended on uptake for growth (45%), and ingested P was either taken up for growth (58%) or spent on defecation (34%). Overall, nutrient uptake reflected the smolt sludge composition rather than nutrient requirements for H. diversicolor, which may be a short-term effect and needs to be investigated further. The flow of nutrients was strongly affected by feed supply, as ingestion, defecation, excretion, and uptake for growth were significantly higher in the high feed supply group than in the low feed supply group.